The role of the family in promoting drug free communities in Nigeria. - Ahmad Tajuddin Othman, Hamisu Mamman; Lim, Hooi Lian (Universiti Sains Malaysia, 2014)
Drug abuse is rapidly growing worldwide problem. The problem of drug abuse poses a significant threat to the health, economic, and social structure of families, communities and the nations.